J2EE™ Platform Web Services - Lai, Ray (Java 2 platform, enterprise edition series., 2003)
Build robust, scalable, end-to-end business solutions with J2EE™ Web Services. This is the definitive practitioner's guide to building enterprise-class J2EE Web Services that integrate with any B2B application and interoperate with any legacy system. Sun senior architect Ray Lai introduces 25 vendor-independent architectural patterns and best practices for designing Web Services that deliver outstanding performance, scalability, and reliability. Lai takes you to the frontiers of emerging Web Services technologies, showing how to make the most of today's leading-edge tools, from Java Web Services Developer Pack to Apache Axis. Coverage includes: Web Services: making the business case, and overcoming the technical and business challenges Real-life examples and scenarios, and a start-to-finish application case study Expert guidance on reducing risk and avoiding implementation pitfalls Building complete business solutions with rich messaging and workflow collaboration Mainframe interoperability and B2B integration within and beyond the enterprise Framework and methodology to develop your Web Services patterns and best practices Up-to-the-minute coverage of Web Services security New applications: service consolidation, wireless, and more An extensive library of links to Web resources, reference material, and vendors Whether you're an architect, designer, project leader, or developer, these are the best practices, patterns, and techniques you need to succeed with Web services in your enterprise environment. Enterprises seeking to leverage Web Services to revolutionize the ways they deliver services to customers, partners, and employees will find the answers they need in this book. "Ray Lai's J2EETM Platform Web Services is a comprehensive look at J2EE platform architecture and should be a must read for any serious Web Services developer." -Larry Tabb, Senior Strategic Advisor, Tower Group "This is a book for true practitioners. It's for those interested in designing and implementing Web Services now-and preparing for new opportunities on the horizon." -Jonathan Schwartz, Executive Vice President, Sun Microsystems.